The Effect Of Esg On Firm Value: The Mediating Role Of Financial Performance And The Moderating Role Of Firm Size (Evidence From Manufacturing Companies Listed On The Indonesia Stock Exchange) - Ade Dwi Utama; Sayu Ketut Sutrisna Dewi (Return : Study of Management, Economic and Bussines, 2026)
Firm value reflects management’s success in creating shareholder wealth and represents market perceptions of a company’s long-term prospects. As attention to Environmental, Social, and Governance (ESG) practices continues to grow, ESG has increasingly been viewed as a factor that may influence firm value. However, prior empirical evidence on this relationship remains mixed. This study examines the effect of ESG on firm value by employing financial performance as a mediating variable and firm size as a moderating variable. The sample was selected using purposive sampling and consists of 45 manufacturing companies listed on the Indonesia Stock Exchange over a three-year observation period (135 firm-year). Data were analyzed using path analysis, the Sobel mediation test, and moderated regression analysis. The results indicate that ESG has a positive effect on firm value, while ESG does not significantly affect financial performance. Financial performance is found to positively influence firm value but does not mediate the relationship between ESG and firm value. In addition, firm size does not moderate the effect of ESG on firm value. These findings suggest that ESG influences firm value primarily through a direct relationship and remains consistent across different firm sizes.